Effect of boiling and roasting processing on nutritional quality of two Sudanese peanuts (Arachis hypogaea) cultivars - Hind A. E. Eltom; Mashair A. Sulieman; Amro B. Hassan (Legume Science, 2023)
Abstract This study was conducted to investigate the effect of boiling, roasting and boiling followed by roasting treatments on the nutritional quality of two Sudanese peanut cultivars, Sodari and Madani. Both cultivars are rich in fat content, protein content and bioavailability of macroelements and microelements. The thermal treatments were critical, reduced the antinutrients factors, and significantly (P < 0.05) enhanced the in vitro protein digestibility of the peanut samples. The highest values 78% and 79.2%, for Madani and Sodari cultivars, were obtained after boiling and roasting processing. However, the thermal processing caused a reduction in the vitamin E content of peanuts. In general, boiled and roasted peanuts could serve as a critical, underutilized by‐product, particularly after combining boiling and roasting treatments, for potential applications in food formulations.